A GUIDELINE FOR DEVELOPING AN INITIAL HYDROLOGICAL MONITORING NETWORK AS A BASIS FOR WATER MANAGEMENT IN ARTIFICIALLY DRAINED WETLANDS1. (1st July 2013) - Fahle, Marcus; Dietrich, Ottfried; Lischeid, Gunnar
ABSTRACT Reliable hydrological monitoring is the basis for sound water management in drained wetlands. Since statistical methods cannot be employed for unobserved or sparsely monitored areas, the primary design (first set‐up) may be arbitrary in most instances. The objective of this paper is therefore to provide a guideline for designing the initial hydrological monitoring network. A scheme is developed that handles different parts of monitoring and hydrometry in wetlands, focusing on the positioning of surface water and groundwater gauges. For placement of the former, control units are used which correspond to areas whose water levels can be regulated separately. The latter are arranged depending on hydrological response units, defined by combinations of soil type and land use, and the chosen surface water monitoring sites. A practical application of the approach is shown for an investigation area in the Spreewald region in north‐east Germany. The presented scheme leaves a certain degree of freedom to its user, allowing the inclusion of expert knowledge or special concerns. Based on easily obtainable data, the developed hydrological network serves as a first step in the iterative procedure of monitoring network optimisation. Copyright © 2013 John Wiley & Sons, Ltd.